個と共同体との関係性を築く古典学習指導 : 大村はまの単元学習指導「古典へのとびら」(昭34)を中心に - 坂東 智子; BANDO Tomoko (国語科教育, 2010)
This paper has adopted "Ohgi no Mato" as an effective and practical theme of study on the basis of a survey of "The Door to the Classics" by Hama Ohmura. The survey proves the respondent how deep students' in depth understanding students understand the of classical literature in terms of actual numerical figures. In the meeting they had based on surveyed data, learners accept the people's thoughts and concepts of beauty in community in terms of "Ohgi no Mato," namely study of the classical literature is becoming meaningful. By this survey study, it is made itself cleared has clarified that learners recognize identify with the community through a common language and that through it, they also become conscious of the importance of public relations.